Clear cell (glycogen-rich) gastric adenocarcinoma. - Govender, D; Ramdial, P; Clarke, B; Chetty, R (2004)
Clear cells have been described in many tumors of varying differentiation. Although clear cell carcinoma is well-recognized in the lower urinary and female genital tracts, its occurrence in the gastrointestinal tract and related structures is uncommon. There have been only a few case reports and small series reporting this morphologic phenomenon in the stomach, colon, and biliary tract. Clear cell carcinoma of the endometrium has been associated with poor prognosis, but the prognostic significance of clear cells in gastric adenocarcinoma is unknown. Herein we describe three cases of clear cell, glycogen-rich, gastric adenocarcinoma and evaluate the frequently used classification systems for gastric cancer. Two tumors showed a tubulopapillary pattern and one showed a predominantly diffuse sheet-like growth. The proliferation (MIB) index in all cases was approximately 20%. Only case 1 showed focal staining for alpha-fetoprotein and both cases 1 and 2 showed focal carcinoembryonic antigen reactivity. In conclusion, we describe three cases of clear cell gastric carcinoma that presented as high-stage disease.